Tendency of Malnutrition in Intensive Phase Pulmonary Tuberculosis Patients with Low Macro Nutrient Adequacy - Esti Trihanifah; Stefania Widya Setyaningtyas (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2021)
ABSTRACTBackgrounds:Infectious diseases such as pulmonary tuberculosis are often found in developing countries, not least in Indonesia. When infected, the body will experience hyper-catabolism so that the fulfillment of the needs of macronutrient intake is needed so as not to occur malnutrition especially in the intensive phase.Objectives: This study aims to determine and analyze the relationship between the level of energy and macro nutrient adequacy with the nutritional status of intensive pulmonary tuberculosis patients.Methods:This study used a cross sectional research design with a sample of 32 respondents. The sample selection procedure used purposive sampling technique. Retrieval of data in this study using a 2x24 hour food recall questionnaire. Data analysis using the chi-square test with SPSS softwareResults: Based on the analysis that has been done, the results show that the adequacy of energy p=0.001 (OR=17.0) and macro nutrients (protein p=0.000 (OR=17.0); fat p=0.0001 (OR=3.7) ; carbohydrates p=0.000 (OR=1.0)) is related to the nutritional status of patients with intensive pulmonary tuberculosis.Conclusions: The tuberculosis patient is expected to increase the daily energy and macro nutrition substance to prevent nutrition deficiency for the patient.